2020
DOI: 10.1039/d0cp01204a
|View full text |Cite
|
Sign up to set email alerts
|

Bi-stimuli assisted engineering and control of magnetic phase in monolayer CrOCl

Abstract: Magnetic phase control in two-dimensional CrOCl can be achieved through the application of strain and electric field. This leads to a ferromagnetic to antiferromagnetic phase transition and remarkable enhancement of the Curie temperature to 450 K.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
19
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 28 publications
4
19
0
1
Order By: Relevance
“…The eqn (3) described above has also been used to estimate the critical temperature of several 2D magnetic materials. 22,42 In the current work, considering the first nearest neighbour interaction of spins is enough to obtain a good agreement of the critical temperature with experimentally obtained value. 46 …”
Section: Resultssupporting
confidence: 61%
See 1 more Smart Citation
“…The eqn (3) described above has also been used to estimate the critical temperature of several 2D magnetic materials. 22,42 In the current work, considering the first nearest neighbour interaction of spins is enough to obtain a good agreement of the critical temperature with experimentally obtained value. 46 …”
Section: Resultssupporting
confidence: 61%
“…However, the magnetic properties can be ne-tuned, as desired, through the application of a few engineering techniques. 22,23 Cr 2 Ge 2 Te 6 (CGT) is a newly discovered 2D magnetic material which has gained great attention recently because of its ability to be exfoliated to the monolayer limit 24 similar to that of CrI 3 . 25 Moreover, recent investigations have shown the feasibility of formation of stable heterostructures with several other 2D materials like graphene, 26 CrI 3 27 and topological insulators, 28,29 observation of photoluminescence 30 and magneto-optical effects.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a strong increase with increasing pressure was observed for this lattice distortion, with values much larger than the largest value that can be achieved at low temperatures for ambient pressure. It is suggested that an enhanced monoclinic lattice distortion might play a role for thin-layer and single-layer FeOCl, CrOCl, and VOCl [26,33].…”
Section: Discussionmentioning
confidence: 99%
“…Aside from the strong interest in the fundamental physics of MOCl compounds, a renewed interest in the application of FeOCl-type compounds resulted in reports about the use as catalysts [14][15][16][17], nonlinear optical materials [18], and developments in the context of chloride ion batteries [19][20][21][22][23]. Research on this specific class of compounds was further boosted by the proposal of MOCl as van der Waals heterostructures [24], and their use as two-dimensional (2D) intrinsically magnetic monolayer materials, e.g., for applications in the field of spintronics [25][26][27][28][29][30][31]. Zhang et al [32] reported liquid exfoliation of FeOCl into few-layer thick nanosheets, a feature that was explained by the low cleavage energy of 340 mJ m −2 being close to the value of 320 mJ m −2 for graphite.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the magnetic properties of few-layer samples are also unknown. These issues have been receiving increasing interest recently and have been studied through theoretical calculations. However, due to the complexity of the three filled 3d orbitals, some calculation results are contradictory.…”
Section: Introductionmentioning
confidence: 99%